La Dissémination - Derrida, Jacques 1930-2004 (Paris Seuil, 1972)
In Dissemination - more than in any previous work - Derrida weaves a complex pattern of puns, verbal echoes and allusions, intended to 'deconstruct' both the pretension of criticism to tell the truth about literature, and the pretension of philosophy to be the literature of truth. Dissemination contains three of Derrida's most central and seminal works: 'Plato's Pharmacy', 'The Double Session' and 'Dissemination'. The essays present a re-evaluation of the logic of meaning and the function of writing in Western discourse. This is a groundbreaking work on the relationship and interplay between language, literature and philosophy.
Keywords: Philosophy; Literature